ChemInform Abstract: A Convenient Palladium‐Catalyzed Carbonylative Synthesis of Quinazolines from 2‐Aminobenzylamine and Aryl Bromides. Issue 17 (April 2015) - Chen, Jianbin; Natte, Kishore; Neumann, Helfried; Wu, Xiao‐Feng
Abstract The first carbonylative protocol for the preparation of quinazoline derivatives (IV) (17 examples) is given.